Repetitive hypoxic preconditioning protects retinal ganglion cells against damage caused by exposure to blast - Matthew M. Harper; Nickolas A. Boehme (PLoS ONE, 2026)
Visual system damage and dysfunction caused by exposure to a blast wave has been described in both clinical studies and in pre-clinical models. Within the retina, retinal ganglion cells (RGC) exhibit sensitivity to mild blast-mediated traumatic brain injury (bTBI), which can result in progressive neurodegeneration. The purpose of this study was to determine if repetitive hypoxic preconditioning (HPC) can prevent bTBI-mediated RGC damage and death. This study utilized clinically relevant outcomes of RGC structure and function, supported by histological analysis of the surviving RGCs. Mice were exposed to six sessions of HPC over a two-week period at an 11% oxygen concentration, and subsequently subjected to bTBI using a shock tube. Four-weeks following exposure to bTBI or sham, functional and structural analysis of RGCs was performed using the pattern electroretinogram (PERG) and optical coherence tomography (OCT). BRN3A antibody labeling was subsequently used to quantify the number of RGCs surviving at the termination of the study. Analysis of RGC outcomes showed significantly decreased PERG amplitude and RGC Complex + retinal nerve fiber layer (RNFL) thickness in mice with bTBI compared to sham. There was no significant difference in RGC outcomes between sham mice and HPC+ bTBI mice. Taken together, these results show that HPC can provide at least partial neuroprotection to RGCs prior to blast exposure.